Pengaruh Penerapan Manajemen Berbasis Sekolah terhadap Mutu Pendidikan: Studi Kasus di SDIT Al-Haraki Kota Depok - Maskur, Abu (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2021)
This study aims to determine the effect of implementing school-based management (SBM) on the quality of education at SDIT Al-Haraki Depok City. The method used in this research is quantitative, namely the data obtained in the form of numbers and the analysis emphasizes numerical processing with statistics. The approach used in this research is correlational which aims to see the effect of the implementation of school-based management on the quality of education. The results obtained from this study state that there is a positive and close influence between the implementation of school-based management (SBM) on the quality of education at SDIT Al-Haraki Depok City which is indicated by the correlation coefficient value r = 0.464, it can be obtained the determination R2 = 0.215, which means that the implementation of school-based management (SBM) has contributed 21.5% to improving the quality of education at SDIT Al-Haraki.